Hubungan Proactive Personality dengan Career Adaptability pada Mahasiswa Tingkat Akhir Universitas Negeri Padang - Aritonang, Ikelara; Nio, Suci Rahma (Lembaga Yasin AlSys, 2025)
This study aims to determine the relationship between proactive personality and career adaptability among final-year university students. Low career adaptability can hinder the ability to adjust during the transition from college to the workforce, potentially increasing the open unemployment rate among university graduates. Proactive personality, as a trait that encourages individuals to take initiative and make changes in their lives, is presumed to play a role in shaping career adaptability. The research employed a quantitative approach with a correlational method. The study population consisted of active undergraduate students from the 2018–2021 cohorts, with a sample of 441 students selected through proportionate random sampling. Data were collected using the Career Adapt-Abilities Scale and the Proactive Personality Scale–Short Version, and analyzed using Pearson’s product-moment correlation test. The results showed a correlation coefficient of 0.744 with a significance value of 0.000 (p < 0.05), indicating a significant positive relationship between proactive personality and career adaptability. The higher the proactive personality of final-year students, the higher their career adaptability. Overall, the sample demonstrated high levels in both variables. These findings confirm that the strong link between proactive personality and career adaptability reflects a high level of readiness for the transition from college to the workforce and can serve as a reference for designing career development programs at universities.